Report of the Working Group on District Planning Volume-I - Planning Commission (Planning Commission, 1984)
To make decentralised planning a success, it has to be backed up by sound practices. The capabilities for decentralised planning have to be assiduously built up, the right procedures and suitable structures have to be evolved and necessary technical and administrative changes, including attitudinal changes have to be brought about among the bureaucrats and the politicians.
Government of India, Planning Commission